Use of Social Networks and Hypertext Critical Reading Strategies in University Students - Fuster-Guillén, Doris Elida (2020)
The objective of the present study was to determine if the use of social networks allows the management of hypertextual critical reading strategies in the first year students of the School of Economics of the Federico Villareal National University (Peru), due to the fact that at present Students use technological tools and social networks (RRSS) for the development of their academic activities. Likewise, they use hypertextual critical reading strategies, understood as a combination of texts, sounds and images that results in a text, which generates a multisequential reading and, if necessary, also multilinear. The research method that was applied was the hypothetical deductive, under a non-experimental, transversal design, descriptive of quantitative approach and positivist paradigm. The study population was made up of 150 university students who were administered questionnaires on the use of social networks and hypertextual reading strategies. Both instruments were validated by expert judgment, whose reliability obtained by cronbach's alpha was 0.801 and 0.918 respectively. The result was that the use of social networks allows the management of hypertextual critical reading strategies; It also develops the elements of thought and the verification of critical reasoning.